Unilateral Visual loss Due to Methanol Intoxication: A Case Report - Faraji Dana, Hoorvash; Shojaei Arani, Lida; Bahmani, Kiumars (Student Research in Translational Medicine, 2021)
Methanol is a toxic alcohol which can cause severe bilateral visual impairment. In this study we report a case of unilateral visual loss due to methanol intoxication. A 45-year-old man referred to toxicology department of Loghman Hakim Hospital complaining of bilateral blurred vision, vomiting, nausea. He was oriented and he had drunk about 500 cc alcohol two days ago, he underwent 4 hours of emergency hemodialysis and we also prescribed erythropoietin, Methylprednisolone, Amp folinic acid, Na/HCO3. then he was referred to ophthalmologist that reported: right eye’s acuity 7/10, left eye’s acuity 3m, RADP positive, left eye’s abducent movement and its color was disturbed and retinal examination was consistent with methanol intoxication. Visual impairment due to methanol poisoning usually occurs bilaterally, but rare cases of unilateral vision damage have also been reported in two studies which they stated may be due to anatomical or structural variation.